DIGITALISASI MULYA BIRO JASA UNTUK MENINGKATKAN EFEKTIVITAS PEMASARAN DAN KUALITAS PELAYANAN KEPADA MASYARAKAT DALAM PENGURUSAN PERIZINAN DAN LEGALITAS - Kurniawan, Hendra; Cahyono, Nuri; Nurhayanto, Nurhayanto; Gustafito, Naufal Nuha; Yuliana , Dwi Eva (Gapenas Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, with a total of 64.2 million units contributing 61.07% to the national Gross Domestic Product (GDP), equivalent to IDR 8,573.89 trillion. However, only about 12% of these MSMEs have effectively adopted digital technologies. Digitalization holds a strategic role in enhancing business competitiveness and efficiency in the era of the Industrial Revolution 4.0 toward Society 5.0, particularly in marketing activities that have shifted from conventional systems to digital-based marketing through e-commerce, social media, and online marketplaces. This Community Service Program (PKM) was conducted to assist a partner, Mulya Biro Jasa, an MSME engaged in administrative and legal documentation services located in Kalasan, Sleman, Yogyakarta. Based on observations, the partner faced challenges in marketing and management facilities that remained conventional, such as the absence of an official website, unregistered business location on Google Maps, and underutilization of social media platforms. Through this PKM activity, the implementation team provided several solutions, including the development of a website, social media development, Google Maps optimization, logo design, business cards, and a neon box sign as a business identity. In addition, the implementing team also installed a 1 TB SSD to provide larger digital data storage capacity and added CCTV to enhance the security of important documents. The program successfully improved the partner’s knowledge and skills in utilizing digital technology to support business development. Based on the questionnaire results, the average pre-test score of 3.09 increased to 3.60 in the post-test, indicating a 16,5% improvement in understanding. Furthermore, this activity provided valuable hands-on experience for students in applying information technology knowledge in real-world business contexts.